What Makes Small Firms Grow? Finance, Human Capital, Technical Assistance, and the Business Environment in Romania - J. David Brown; John S. Earle; Dana Lup (W.E. Upjohn Institute for Employment Research, 2003)
Although the development of a new private sector is generally considered crucial to economic transition and development, there has been little empirical research on the determinants of startup firm growth. This paper uses panel data techniques to analyze a survey of 297 new s small enterprises in Romania containing detailed information from the startup date through 2001. We find strong evidence that access to external finance (loans) increases the growth of both employment and sales. Taxes appear to constrain growth. There is some evidence that entrepreneurial skills increase growth, but only weak evidence for the effectiveness of technical assistance, and only when it is provided by foreign partners or international agencies. A wide variety of alternative measures of the business environment (contract enforcement, property rights, and corruption) are tested, but are found to have little or no association with firm growth.
Keywords: M13; O16; O19; P26; 330; Earle; Romania; small; firms; growth